Expanding the phenotypic spectrum of COLEC10‐Related 3MC syndrome: A glimpse into COLEC10‐Related 3MC syndrome in the Ashkenazi Jewish population. Issue 10 (9th August 2022) - Rabin, Rachel; Hirsch, Yoel; Chung, Wendy K.; Ekstein, Josef; Levy‐Lahad, Ephrat; Zuckerman, Shachar; Mor‐Shaked, Hagar; Meiner, Vardiella; Booth, Kevin T.; Pappas, John
Abstract: Bi‐allelic variants in COLEC11 and MASP1 have been associated with 3MC syndrome, a clinical entity made of up four rare autosomal recessive disorders: Carnevale, Mingarelli, Malpuech, and Michels syndromes, characterized by variable expression of facial dysmorphia, cleft lip/palate, postnatal growth deficiency, hearing loss, cognitive impairment, craniosynostosis, radioulnar synostosis, and genital and vesicorenal anomalies. More recently, bi‐allelic variants in COLEC10 have been described to be associated with 3MC syndrome. Syndromic features seen in 3MC syndrome are thought to be due to disruption of the chemoattractant properties that influence neural crest cell migration. We identified nine individuals from five families of Ashkenazi Jewish descent with homozygosity of the c.311G > T (p.Gly104Val) variant in COLEC10 and phenotype consistent with 3MC syndrome. Carrier frequency was calculated among 52, 278 individuals of Jewish descent. Testing revealed 400 carriers out of 39, 750 individuals of Ashkenazi Jewish descent, giving a carrier frequency of 1 in 99 or 1.01%. Molecular protein modeling suggested that the p.Gly104Val substitution alters local conformation. The c.311G > T (p.Gly104Val) variant likely represents a founder variant, and homozygosity is associated with features of 3MC syndrome. 3MC syndrome should be in the differential diagnosis for individuals with short stature, radioulnar synostosis, cleft lip and cleft palate.